Eine frühe mediale Beschäftigung mit der Genderproblematik aus der Männerperspektive – zu Herbert Grönemeyers Popsongtext «Männer» und seinen Folgen (Studia theodisca, 2012)
Pop songs can be used as semiotic signs to give insight into public opinion simply because they have to prove themselves successfull in a commercial environment: they should reflect, not contradict, the general attitudes of the song’s buyers. In this article I will refer to the song «Männer» by Herbert Grönemeyer, questioning whether its text really breaks with traditional role models. I come to a somewhat qualifying answer. However, especially since Grönemeyer does not contradict the old role model, he seems to be credible when he ignores it in his later song «Mensch».